2015
DOI: 10.1007/s11606-015-3234-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Multifaceted Outreach to Initiate Colorectal Cancer Screening in Community Health Centers: A Randomized Controlled Trial

Abstract: INTRODUCTION:Colorectal cancer (CRC) screening rates are low among vulnerable populations. Fecal immunochemical tests (FITs) are one screening modality with few barriers. Studies have shown that outreach can improve CRC screening, but little is known about its effectiveness among individuals with no CRC screening history. We sought to determine whether outreach increases FIT uptake among patients with no CRC screening history compared to usual care. METHODS: This study was a patient-level randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 33 publications
3
74
0
Order By: Relevance
“…The majority of these studies tested the impact of PN on screening rates for colorectal (n = 32 [67%]), breast (n = 13 [27%]), or cervical cancer (n = 4 [8%]) . Thirty‐nine articles reported a significant favorable increase in cancer screening rates for PN intervention groups versus controls . Thirteen studies (27%) targeted African American, Latino, Korean American, Asian/Pacific Islander, and non–US‐born urban minority populations .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies tested the impact of PN on screening rates for colorectal (n = 32 [67%]), breast (n = 13 [27%]), or cervical cancer (n = 4 [8%]) . Thirty‐nine articles reported a significant favorable increase in cancer screening rates for PN intervention groups versus controls . Thirteen studies (27%) targeted African American, Latino, Korean American, Asian/Pacific Islander, and non–US‐born urban minority populations .…”
Section: Resultsmentioning
confidence: 99%
“…10, Thirty-nine articles reported a significant favorable increase in cancer screening rates for PN intervention groups versus controls. 10,[32][33][34][35][37][38][39][41][42][43][44][45][47][48][49][50][51][52][53][54][55][56][58][59][60][61][62][64][65][66]69,[71][72][73][74][75][76]78 Thirteen studies (27%) targeted African American, Latino, Korean American, Asian/Pacific Islander, and non-US-born urban minority populations. 42,47,49,50,52,57,58,65,71,72,…”
Section: Screeningmentioning
confidence: 99%
“…Multiple studies have demonstrated that mailing fecal tests increases CRC screening uptake, but almost all such studies have evaluated screening after only a 1‐time intervention . There is little information on whether an ongoing mailed program improves screening adherence over time, particularly in a setting in which patients also have access to screening colonoscopy and flexible sigmoidoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…2 Multiple studies have demonstrated that mailing fecal tests increases CRC screening uptake, but almost all such studies have evaluated screening after only a 1-time intervention. [3][4][5][6][7][8][9][10][11] There is little information on whether an ongoing mailed program improves screening adherence over time, particularly in a setting in which patients also have access to screening colonoscopy and flexible sigmoidoscopy. Long-term adherence to fecal testing might not be as robust as adherence to the other tests because of its annual testing cycle versus testing every 5 or 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…T he authors conducted a randomized trial of a multidimensional intervention to enhance colorectal cancer (CRC) screening uptake using fecal occult blood tests (FOBT) in a community health center (CHC) setting for patients who had no evidence of prior screening, 1 building on the author's previous work in which mailings sent to patients in this setting achieved higher CRC screening uptake than a multifaceted practice-level systems-based intervention.…”
mentioning
confidence: 99%